Jurisdictional Issues in the Digital Age - Yulia Razmetaeva; Hanna Ponomarova; Iryna Bylya-Sabadash (Ius Humani. Jornal do direito, 2021)
The article addresses some aspects of the key challenges for legal reality and legal systems in the digital age with a focus on jurisdictional issues in special attention to cyberspace, given its independent value and self-regulatory nature. The article suggests that regarding issues through the prism of a universal human rights approach could be a pillar for resolving existing and potential digital conflicts, prevent cybercrimes. The general legal framework in light of this approach is proposed here. The article discusses scenarios for solving jurisdictional problems: (i) global—focuses on the idea that a single worldwide legal framework and a universal regulation mechanism are possible; (ii) fragmented—partly considers the possibility of a single legal framework (or a set of agreements) and rely mainly on regional mechanisms; and (iii) national—each legal system is capable of providing and effective response to the threats of the digital age and aligns its legislation and judicial practice with the latter. Finally, it is suggested to focus on the prevention and mitigation of negative consequences of the activities of all subjects of law.